The role of dopamine in Toxoplasma-induced behavioural alterations in mice: an ethological and ethopharmacological study - Skallová, A; Kodym, P; Frynta, D; Flegr, J (Parasitology, 2006)
Toxoplasma gondii, a cosmopolitan protozoan parasite, is known to induce behavioural alterations in rodents and may exert an effect on human personality and behaviour. The mechanism of parasite-induced alterations in host behaviour has not been described, but it was hypothesized that development of Toxoplasma tissue cysts in the brain could affect the dopaminergic neuromodulatory system. In this study, we tested the effect of latent Toxoplasma infection on mouse behaviour associated with activity of the dopaminergic system, i.e. locomotion in a novel environment and exploration test. Additionally, we examined the behavioural response of Toxoplasma-infected mice to a selective dopamine uptake inhibitor, GBR 12909. In both genders, Toxoplasma infection decreased locomotion in the open field. Infected females displayed an increased level of exploration in the holeboard test. GBR 12909 induced suppression in holeboard-exploration in the infected males, but had an opposite effect on the controls. These results suggest an association between Toxoplasma gondii infection and changes in the dopaminergic neuromodulatory system.
Keywords: pátrací chování; mozek; dopamin; chování zvířat; Breeding; toxoplazmóza; lokomoce; Female; Toxoplasmosis; Dopamine Uptake Inhibitors; injekce intraperitoneální; chov; myši inbrední BALB C; zvířata; myši; inhibitory vychytávání dopaminu; Exploratory Behavior; Injections, Intraperitoneal; Mice; ženské pohlaví; Toxoplasma; Male; Brain; piperaziny; Dopamine; Locomotion; Piperazines; Animals; mužské pohlaví; Behavior, Animal; Mice, Inbred BALB C